The influence of perinatal high-risk behavior on maternal and neonatal health - Maryam Kianpour; Zahra Babaahmady Milany; Masoume Pirhadi (Journal of Education and Health Promotion)
BACKGROUND: Given the relatively high incidence of cigarette and hookah use in Iran, coupled with their detrimental effects on both mother and fetus, this study primarily aims to explore the correlation between cigarette and hookah smoking during pregnancy and the intensity of pain, duration of the first, second, and third stages of labor, weight of the placenta, and anthropometric measurements of neonates. MATERIALS AND METHODS: This cross-sectional study involved 174 pregnant women in Isfahan, Iran, in 2022. Participants were chosen based on specific inclusion criteria and were categorized into two groups: those exposed to both passive and active smoke (n = 87) and those unexposed (n = 87). Labor pain, duration of labor stages, and placenta weight were assessed using the Visual Pain Scale, a stopwatch, and a digital scale, respectively, and were documented in a checklist. RESULTS: The duration of labor stages in the smoke-exposed group was significantly longer than that in the nonexposed group. Moreover, the smoke-exposed group experienced higher pain intensity than in the nonexposed (P < 0.001). The mean neonate birth weight (2906.35 ± 419.62 vs. 3137.81 ± 342.76, P < 0.001), placenta weight (364.18 ± 64.97 vs. 419.21 ± 52.66, P < 0.001), and head circumference (34.27 ± 2.55 vs. 34.46 ± 1.29, P = 0.015) in the exposed group were significantly lower than those in the nonexposed group (P < 0.001). CONCLUSIONS: Exposure to both passive and active cigarette and hookah smoke during pregnancy has a detrimental impact on neonate anthropometrics, pain intensity, and the duration of labor.